PENGGUNAAN LAYANAN KONSELING KELOMPOK UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VII - Heri Setiawan; Yusmansyah Yusmansyah; Diah Utaminingsih (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this research was to know the increasing of student’s study motivation by using group counseling service at grade VII SMPN 1 Ambarawa year of 2012/2013. Method of this research is quasi experimental method teqhnique of one-group pretest-posttest design. Subject of this research are 6 students of grade VII that have low study motivation. Technique in gained the data of this research is by using study motivation scale. Result of this research showed that the students’ study motivation can increase by using group counselling, it showed from the data analysis that use wilcoxon test, from the result of pretest and posttest gained Zoutput Ztabel ( -2,201 -1,960) so, Ho is rejected and Ha is received, it means that the students’ study motivation can increase by using counselling group. Conclusion of this research is study motivation can increase by using counselling group of the students at grade VII SMPN 1 Ambarawa year of 2012/2013. The suggestions are for teacher Guidance and Counselling (BK) should apply counselling group in increasing the students’ study motivation.kata kunci : bimbingan konseling, konseling kelompok, motivasi belajar